Detection of Theileria equi, Babesia caballi, and Anaplasma phagocytophilum DNA in Soft Ticks and Horses at Ciudad Juarez, Mexico - Medrano-Bugarini, Raúl Alejandro (2019)
Currently, ticks are second in transmission of pathological agents to humans, and in the veterinary field are ranked first. Thus, pathogens that might be in contact with human and animal populations, especially farm animals such as horses, Equus caballus (Linnaeus), should be identified. Two species of soft ticks in the Argasidae family, Otobius megnini (Duges) and Ornithodoros turicata (Duges), and one hard tick of the Ixodidae family, Rhipicephalus sanguineus (Latreille) were identified. DNA of pathogens Theileria equi (Laveran), Babesia caballi (Nuttall and Strickland), and Anaplasma phagocytophilum (Foggie) that have been reported in species of hard ticks but not soft ticks were identified. Overall, 144 blood samples from horses at Ciudad Juárez, Chihuahua, Mexico, were processed for DNA extraction, and analyzed by end-point or nested PCR to identify pathogens. The prevalence of T. equi was 6.9% (10/144) and 5.9% (3/51) in blood samples and soft tick samples, respectively; the prevalence of B. caballi was 2.8% (4/144) in blood samples and 5.9% (3/51) in soft ticks. There was one case of coinfection with both pathogens, and one blood sample tested positive for A. phagocytophilum, indicating a prevalence of 0.8% (1/124). The results suggested that soft ticks evaluated are potential vectors and might play a role in transmission of the pathogens.